Photocatalytic Degradation of Acid Black 210 dye Using Fixed Bed Reactor Containing Zinc Oxide Nanoparticles: Effects and Box–Behnken Optimization - Zahraa A. Najm; Mohammed A. Atiya; Ahmed K. Hassan (Iraqi Journal of Industrial Research, 2025)
The present study uses a continuous photo-catalytic approach to treat textile wastewater with Acid Black 210 (AB210). In an extract from eucalyptus leaves, zinc oxide nanoparticles (ZnO-NPs) were created using a liquid-phase reduction technique and utilized as heterogeneous catalysts. SEM, EDAX, and FTIR procedures were among the characterization methods used on (NPs). The produced NPs had a specific surface area of 26 m2 /g and were discovered to be spherical and porous. The effect of the main parameters on the Photo-Catalytic degradation of AB210 was investigated through a continuous fixed-bed system. A photoreactor was used to investigate and analyze the variables affecting the continuous system the dye concentration (5–40 mg/L), the pollutant flow rate through the column (AB210 flow rate) (1–5 mL/min), the height of the catalyst inside the column (ZnO-NPs height) (0.5–1.5 cm), and the UV-intensity (6–24 W/m2). The optimized parameters for the fixed-bed system were with a removal efficiency of 69% determined as 2.25 mL/min, 1.21 cm, 30 mg/L, and 15 W/m2 for flow rate, ZnO-NPs height, AB210 concentration, and UV intensity respectively. This study demonstrates the potential of ZnO-NPs synthesized from green sources as effective catalysts in the treatment of dye-contaminated textile wastewater using a continuous photo-catalytic system.